The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/dev.21814
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and exploratory behavior in the African striped mouse, Rhabdomys, taxa are partially modified by the physical rearing environment

Abstract: The environment may modulate genetic influences on behavioral expression. We investigated whether the physical rearing environment modulates anxiety and exploratory behavior in four populations, representing three species, of the striped mouse Rhabdomys. One population originated from an arid, open habitat and the others from grassy, covered habitats, and two species occurred in sympatry. We raised captive individuals of all populations in treatments that simulated cover or no cover for two generations and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Similarly, female degus huddled as frequently with stranger females as they did with familiar females although interactions with strangers were typically more agonistic(Insel et al, 2020). Differences in amicability between individuals of different Rhabdomys taxa suggest that the causal mechanism for social preference may differ in the genus.Personality experiments in non-social contexts have shown that R. pumilio is comparatively less anxious and bolder than R. d. chakae(Mackay & Pillay, 2021;Rymer & Pillay, 2012) which is partially modulated by rearing environment and a result of phylogenetic differences between taxa(Mackay & Pillay, 2019). We found that R. pumilio approached stimulus females faster and investigated them for longer than R. d. chakae, regardless of stimulus type.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Similarly, female degus huddled as frequently with stranger females as they did with familiar females although interactions with strangers were typically more agonistic(Insel et al, 2020). Differences in amicability between individuals of different Rhabdomys taxa suggest that the causal mechanism for social preference may differ in the genus.Personality experiments in non-social contexts have shown that R. pumilio is comparatively less anxious and bolder than R. d. chakae(Mackay & Pillay, 2021;Rymer & Pillay, 2012) which is partially modulated by rearing environment and a result of phylogenetic differences between taxa(Mackay & Pillay, 2019). We found that R. pumilio approached stimulus females faster and investigated them for longer than R. d. chakae, regardless of stimulus type.…”
mentioning
confidence: 57%
“…Personality experiments in non‐social contexts have shown that R. pumilio is comparatively less anxious and bolder than R. d. chakae (Mackay & Pillay, 2021; Rymer & Pillay, 2012) which is partially modulated by rearing environment and a result of phylogenetic differences between taxa (Mackay & Pillay, 2019). We found that R. pumilio approached stimulus females faster and investigated them for longer than R. d. chakae , regardless of stimulus type.…”
Section: Discussionmentioning
confidence: 99%
“…The OF consisted of a glass tank (46 × 30 × 35 cm) with opaque sides. The tank floor was divided into nine equal squares using electrical tape, which did not impede movement of a mouse in the current or any of our previous studies (Mackay & Pillay, 2019; Rymer & Pillay, 2012; Rymer et al, 2008). A single mouse was placed in the center of the tank.…”
Section: Methodsmentioning
confidence: 99%